Sejarah Pendidikan di Kota Barus pada Masa Kolonial - Pulung Sumantri; Aditya Darma; Latifah Hanum (Keguruan, 2021)
Barus is an ancient city, town, and city of exchange around the world going back hundreds of years, especially between the 12th and 17th hundreds of years AD. In its long history, Barus has been an exporter of crops, for example, tar, frankincense, camphor, pepper, animal skins and others. With the emergence of the Dutch for Indonesian education gave a frame of primitive society, on the grounds that schools were coordinated by the colonial government. Techniques carried out in review. This is a technique or approach to writing that can be described as a development of exercises related to the techniques of miscellaneous library information, perusing, and recording. and study interaction materials. The Dutch opened an educational institution in Barus, one of which was so that the Batak people could have the Dutch in their space. So the Dutch government has control over Sibolga, especially Barus. Improvement of schools for the Batak nation by the Dutch, recently followed by rebuilding which has been carried out by zending. To grow its territory and to accelerate the course of social change, the Dutch government established schools.